Dendrimer Anion-Exchange Stationary Phase for Separation of Oligonucleotides - Sylwia Studzińska; Szymon Bocian; Anna Kilanowska; Bogusław Buszewski (Molecules, 2022)
Oligonucleotides are used in many research areas. Thus, there is a need for their successful separation methods. Ion-exchange chromatography is the most popular separation technique, but it has limitations for these compounds. For this reason, new stationary phases are developed in order to increase separation selectivity. This study aimed to apply a series of dendrimer anion exchangers with various bonded layers to separate oligonucleotides by using different mobile phases to find conditions that allow sufficient separation. The number of anion-exchange layers, type of salt, and pH significantly impacted the oligonucleotide analysis. The developed chromatographic method was characterized by adequate selectivity for oligonucleotides differing in sequence length. It is essential to underline that the number of bonded layers appeared to have a significant influence, and the three layers appeared optimal. Based on our results, it may be concluded that the dendrimer stationary phases can be successfully used as an alternative to commonly applied packing materials in ion-exchange chromatography.